Quality Management and Education Financing during the COVID-19 Period at UISU Siantar Private High School - Yuniarto Mudjisusatyo; Dian Ratna Puri; Enjel Oktaviany Simanjuntak; Hilmi Saputri Nasution; Petrus Sanjaya Simarmata (Community Medicine and Education Journal, 2022)
During the pandemic, the Ministry of Education, Research, and Technology of the Republic of Indonesia launched a policy of flexibility in the use of school operational assistance funds (BOS). This policy aims to make school principals as managers in schools able to adjust the budget for school needs in accordance with conditions during the COVID-19 pandemic. This study aims to describe the quality management and financing of education during the COVID-19 period at the UISU Siantar Private High School. This research is descriptive research. Data were collected through observation, literature study, document analysis, and interviews. The results showed that UISU Siantar Private High School had managed education financing in accordance with government expectations and BOS fund management standards. In the future, it is hoped that the management of the UISU Siantar Private High School, especially the principal and treasurer, will continue to be responsive and transparent in the preparation of school activities and budgets (RKAS) and the use of BOS funds, especially regarding the COVID-19 pandemic, which has not been completed until now.